2016
DOI: 10.1016/j.freeradbiomed.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

DHA-induced stress response in human colon cancer cells – Focus on oxidative stress and autophagy

Abstract: Polyunsaturated fatty acids (PUFAs) are important constituents of the diet and health benefits of omega-3/n-3 PUFAs, especially eicosapentaenoic acid (EPA, 20:5 n-3) and docosahexaenoic acid (DHA, 22:6 n-3) have been well documented in relation to several diseases. Increasing evidence suggests that n-3 PUFAs may have anticancer activity and improve the effect of conventional cancer therapy. The mechanisms behind these effects are still unclear and need to be elucidated. We have examined the DHA-induced stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 53 publications
7
39
0
1
Order By: Relevance
“…Several studies also showed that the tumor suppressive effects of DHA may be accelerated by increased cellular oxidative stress [2, 17, 18, 54]. Coincidentally, DSF and its metabolites have been shown repeatedly to cause a pro-oxidative environment in cancer cells [17, 23, 26, 36]. Therefore, it is not surprising that the combination of DSF and DHA causes significantly higher oxidative pressure as indicated by enhanced HO-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also showed that the tumor suppressive effects of DHA may be accelerated by increased cellular oxidative stress [2, 17, 18, 54]. Coincidentally, DSF and its metabolites have been shown repeatedly to cause a pro-oxidative environment in cancer cells [17, 23, 26, 36]. Therefore, it is not surprising that the combination of DSF and DHA causes significantly higher oxidative pressure as indicated by enhanced HO-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DHA induced the mRNA expression of TNF-α through post-transcriptional regulation by the downregulation of microRNA-21 expression. A recent study compared DHA-induced stress responses in two human colon cancer cell lines, SW620 and Caco-2 [54]. DHA inhibited the growth of SW620 cells at early time points while that of the Caco-2 cells was unaffected by the same treatment.…”
Section: Dha Induces Apoptotic Signaling and Affects Dna Damage Rementioning
confidence: 99%
“…Moreover, the mechanism by which DHA inhibits tumor cell growth apparently differs among tumors. Some research studies have demonstrated that DHA induces cancer cell apoptosis via reactive oxygen species (ROS) production in prostate cancer [22], and colon cancer [23, 24]. However, a few studies have also suggested that DHA inhibits cancer cell growth by inducing oxidative stress in liver cancer [25].…”
Section: Introductionmentioning
confidence: 99%